2016
DOI: 10.1103/physrevb.94.104512
|View full text |Cite
|
Sign up to set email alerts
|

Superconducting properties of noncentrosymmetricNb0.18Re0.82thin films probed by transport and tunneling experiments

Abstract: Superconducting thin films of the noncentrosymmetric superconductor Nb 0.18 Re 0.82 were successfully deposited by UHV sputtering technique. X-ray diffraction analysis indicated that the films are polycrystalline, with a preferential (nn0) orientation and the lattice parameter in agreement with the expected single α-Mn cubic phase. A detailed electrical characterization of the samples as a function of the thickness (3.5 nm d 142 nm) was performed both in the normal and in the superconducting states, revealing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 64 publications
1
26
0
Order By: Relevance
“…The morphology and roughness of the film surface strongly affect its transport properties, like, for instance, the value of the resistivity. In the case of NbRe and NbReN structural characterization revealed that the films consist of small crystallites, which are responsible of disorder-dominated electrical conduction [6,8]. The AFM analysis presented in this work confirms this picture.…”
Section: Morphological Propertiessupporting
confidence: 72%
See 1 more Smart Citation
“…The morphology and roughness of the film surface strongly affect its transport properties, like, for instance, the value of the resistivity. In the case of NbRe and NbReN structural characterization revealed that the films consist of small crystallites, which are responsible of disorder-dominated electrical conduction [6,8]. The AFM analysis presented in this work confirms this picture.…”
Section: Morphological Propertiessupporting
confidence: 72%
“…Recently, NbRe-based superconducting films were proposed for the realization of fast SNSPDs, namely NbRe [6,7] and NbReN [8]. In this respect, a detailed characterization of the films is useful to clarify if these two materials may indeed represent a solid alternative to the other well-established superconductors used in this field, such as NbN [10], NbTiN [11], or amorphous WSi [12].…”
mentioning
confidence: 99%
“…Among NCS that are superconductor at ambient pressure, evidence of nodes in the superconducting energy gap has been obtained for Li 2 Pt 3 B 2,3 , Y 2 C 3 4 and CePt 3 Si 5,6 , though in the last one study of parity broken superconducting state is complicated by coexistence of antiferromagnetic order. Yet many other compounds, such as BiPd 710 , Nb 0.18 Re 0.82 11,12 , Re 3 W 13 , PbTaSe 2 14 exhibit fully open superconducting gap while some of them show evidence for multiband superconductivity 11,12 . Recently, the superconducting state of the NCS, Re 6 Zr with the α-Mn cubic structure 15 has called for particular attention.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, NbRe-based superconducting films were proposed for the realization of fast SNSPDs, namely NbRe 6 , 7 and NbReN 8 . In this respect, a detailed characterization of the films is useful to clarify if these two materials may indeed represent a solid alternative to the other well-established superconductors used in this field, such as NbN 9 , NbTiN 10 , or amorphous WSi 11 .…”
Section: Introductionmentioning
confidence: 99%